Customer satisfaction with complaint resolution in the power sector in a developing economy - Andaleeb, Syed Saad; Huda, S. S M Sadrul; Akhtar, Afsana; Dilshad, Segufta (© 2012 Taylor and Francis Group, LLC., 2016)
This article was published in the Journal of Nonprofit and Public Sector Marketing [©2012 Published by Taylor and Francis Group, LLC.] and the definite version is available at: http://doi.org/10.1080/10495142.2012.705178 The Article's website is at: http://www.tandfonline.com/doi/abs/10.1080/10495142.2012.705178